Manifestasi klinis tipe kandidiasis oral pada penderita AIDS di Rumah Sakit Dr Wahidin Sudirohusodo, Makassar (Clinical manifestations of oral candidiasis types in AIDS patients at Dr Wahidin Sudirohusodo Hospital, Makassar) - Sumintarti Sumintarti; Andi Rasdiana S (Journal of Dentomaxillofacial Science, 2014)
Oral candidiasis is one of clinical manifestations in aquired immune deficiency syndrome (AIDS) patients. This conditionis a common opportunistic infection of the oral cavity caused by an overgrowth of Candida spesies. The clinical types oforal candidiasis are erythematous or atropic, pseudomembranous, hyperplastic or chronic, and angular cheilitis. AIDS isgroup of symptoms that resulting from infection of human immunodeficiency virus (HIV). This case is associated with thedecreasing of CD4 count. The aimof this study was to know the types of oral candidiasis on AIDS patients at Dr WahidinSudirohusodo Hospital. This observational studywith a cross-sectional design examined 30 patients with AIDS whosuffered fromoral candidiasis, to determine its type after the diagnosis had confirmed by culture test. Their CD4 cellcount taken fromtheir medical records. The result showed that Pseudomembranous candidiasis were found to be higher(76.7%), that was followed by angular cheilitis (23.3%), hyperplastic (16.7%), and erythematous (6.7%). They wereshowed showed CD4 T cell count <200 cells/mm3 (63.3%). From this study, it was concluded that pseudomembranous candidiasis is the most common type and showed that CD4 T cell count <200cells/mmfrom the AIDS patients.